Populist Discourses on Social Media: Analysis of the Candidates' Twitter Posts in the Local Election Process of March 31, 2019 - Sen, Ayse Fulya; Yenigun Altin, Sule (Marmara Univ, Fac Communication, 2020)
In this study, which aims to show how populist discourses are used as a form of political communication, the forms of populist discourse of the mayoral candidates representing political alliances in the 31 March 2019 local elections were examined. In the 2019 local elections, Twitter sharing of the candidates of the People's and Nation's alliances of the three major cities using Twitter effectively were analyzed through critical discourse analysis and content analysis. By utilizing Ruth Wodak's analysis categories related to populist discourses, the populist discourses of the candidates of the AK Party and the Republican People's Party (CHP) during the election campaigns were analyzed. In the content analysis, it was identified how often the candidates used these words through keywords containing populist elements. In addition, by using the Twitonomy application, it was aimed to measure the popularity of the candidates over the amount of tweet and retweet numbers and their interaction levels during the three-month election campaign. As a result of the study, it was found that the elements of populism were included in the discourses of both alliances, but the canditates of AK Party, which is the main component of the People's alliance, had further populist discourses. It was concluded that the populist discourse strategies determined by Wodak were used prominently in political discourses.
Keywords: Populism; Populist Discourse; Critical Discourse Analysis; AK Party; CHP